Photocatalytic Degredation of Acid Alizarin Black Using Powder and Nanoparticles of Titanium Dioxide - Hayda A. Mohammad Salim; Sherwan M. Simo; Neewar A. Yaseen (Science Journal of University of Zakho, 2014)
Photocatalytic degradation of acid alizarin black (AAB) dye (C.I. 21725) in aqueous solution was investigated using UV light in the presence of powder of titanium dioxide (P- TiO2) and nanoparticles of titanium dioxide (N- TiO2) as a catalyst. The operating conditions were catalyst dosage (10 and 20 mg/L) and initial concentration of AAB dye (10 and 20 mg/L). It was found that the increasing of catalyst concentration enhanced the dye decolourisation. Both catalysts exerted positive effects on the AAB removal whilst the initial concentration of AAB negatively affected its removal.